Arbitrator Neutrality in Alternative Sharia Banking Dispute Resolution: Instruments for Consumer Protection - Bustanul Arifien Rusydi (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the form of legal protection for consumers who are in dispute with Islamic banking institutions through arbitration forums. Implementation of Financial Services Authority Regulation Number 61/POJK.07/2020, namely the establishment of an Alternative Institution for Financial Services Sector Dispute Resolution (LAPS JK), one of the dispute resolution mechanisms through arbitration. The appointed arbitrator is obtained from the internal procedures carried out by the institution. So that there is potential for arbitrators to be non-neutral in examining cases that affect the protection of Islamic banking consumers. The type of research used is qualitative research with a normative approach. Data collection was carried out through a desk-review process, while the analysis process was carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that even though the arbiters who examine cases between consumers and Islamic banking institutions come from Alternative Dispute Resolution Institutions, one of which is the Association of Indonesian Sharia Banks (ASBISINDO), the neutrality of these arbiters has been supervised by the existence of a code of ethics that has been established by the institution. If the arbiter is proven not to be neutral in examining a case, then there is a mechanism for enforcing the code of ethics. So that the potential for conflicts of interest in alternative dispute resolution through arbitration between Islamic banking institutions and their consumers can be avoided.